1999
DOI: 10.1017/s0022215100144275
|View full text |Cite
|
Sign up to set email alerts
|

Anti-neutrophil cytoplasmic antibody-associated mucocutaneous allergic vasculitis with oral manifestations caused by propylthiouracil

Abstract: A 49-year-old woman treated with increasing dosage of propylthiouracil (PTU) in order to control hyperthyroidism, developed progressive necrotic ulcers in the oral cavity, oropharynx and rhinopharynx and vasculitic ulcers on both auricular pinnae after a few days. The PTU treatment was immediately discontinued and the mucosal and skin manifestations resolved promptly. Laboratory findings, including anti-neutrophil cytoplasmic antibodies (ANCA), suggested allergic vasculitis. This is to our knowledge the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…PTU is theoretically preferred over methimazole (MMZ, another thioamide drug) in Graves disease relapse during the postpartum period because of its lower milk:serum concentration ratio [1]. However, PTU is associated with various side effects, including transient leukopenia [2], jaundice, hepatomegaly [3,4], and vasculitis [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…PTU is theoretically preferred over methimazole (MMZ, another thioamide drug) in Graves disease relapse during the postpartum period because of its lower milk:serum concentration ratio [1]. However, PTU is associated with various side effects, including transient leukopenia [2], jaundice, hepatomegaly [3,4], and vasculitis [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…There are several published reports indicating the relationship between treatment with PTU and the occurrence of ANCA positivity with mucosal membrane ulcers 2,8–10 . A woman receiving PTU therapy for Graves’ disease and having ANCA‐associated oral vasculitic lesions is described here.…”
Section: Reported Cases Of Anca‐associated Oral and Mucosal Manifestamentioning
confidence: 93%
“…They found clinical improvement in all patients and the disappearance or concomitant fall in ANCA titres on withdrawal of PTU, suggesting the pathophysiological role of the drug in the development of ANCA‐associated vasculitic disorders 2 . Circulating immune complexes and environmental triggers have been suggested as the probable cause, but the aetiology of ANCA‐associated vasculitis is not known 4,8 . Even though ANCA level usually rises within a few weeks of PTU therapy, it may occur several months or even years later.…”
Section: Reported Cases Of Anca‐associated Oral and Mucosal Manifestamentioning
confidence: 99%
See 1 more Smart Citation
“…As for the causes of renal dysfunction during treatment for Graves' disease, anti-thyroid drugs should be mentioned (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Onthe other hand, previous case reports suggested that some kinds of renal diseases could be complicated by thyroid diseases and that thyroid tissue might serve as a continuous source of antigen for the formation of the nephritogenic circulating immunecomplexes consisting of thyroid constituents and antibody (8-10).…”
Section: Case Reportmentioning
confidence: 99%